"Creative, Good Will for All Men:" Martin Luther King Jr. the Moralist. (31st May 2021) - Hanagan, Nora
Abstract: This essay considers how Ruth Grant's understanding of hypocrisy and integrity might be applied to Martin Luther King Jr. Putting Grant and King in conversation, I argue, helps democratic citizens and theorists think about political ethics in contexts of extreme inequality.